2020
DOI: 10.1016/j.heliyon.2020.e03411
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and antioxidant activity of coconut cotyledon

Abstract: Coconut tree (Cocos nucifera L.), a perennial, monocot tree, belonging to the family Arecaceae, is distributed through the tropics. Bioactivities of coconut water, husk fiber, oil, flowers, spadix and mesocarp of coconut fruit are widely reported. However, there is no study on cotyledon of coconut. In this study, carbohydrates, proteins, lipids, phenols, flavonoids, tannins, alkaloids and antioxidants were quantified in hot and cold percolated extracts of coconut cotyledon. Further, the antioxidant activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…Corresponding outcomes were reported by Haque et al [35], in crude methanolic extract of S. villosa bark (IC 50 value 27.28 μg/ml), and Dillak et al [36], in the ethanolic extract of S. quadrifida root (IC 50 value 20.55 ± 0.42). The result derived from this analysis was in good agreement towards earlier reports suggesting the use of methanol extract for the radical scavenging activity analysis [37]. Different metabolic processes of the living system produce reactive species called free radicals; they spread throughout the body and damage important biomolecules of the body by disrupting their structure and interfering with their function, leading to cellular dysfunction and cell death.…”
Section: Discussionsupporting
confidence: 90%
“…Corresponding outcomes were reported by Haque et al [35], in crude methanolic extract of S. villosa bark (IC 50 value 27.28 μg/ml), and Dillak et al [36], in the ethanolic extract of S. quadrifida root (IC 50 value 20.55 ± 0.42). The result derived from this analysis was in good agreement towards earlier reports suggesting the use of methanol extract for the radical scavenging activity analysis [37]. Different metabolic processes of the living system produce reactive species called free radicals; they spread throughout the body and damage important biomolecules of the body by disrupting their structure and interfering with their function, leading to cellular dysfunction and cell death.…”
Section: Discussionsupporting
confidence: 90%
“…Tannin and alkaloids were proved to be having anti-ulcer activity, which prevents ulceration 12 . The presence of phenolic compounds acts as antioxidant, that reduces the formation of free radicals and thus potentially protects the cell from oxidative damage 13 . An analytical study on the formulation revealed higher alkalinity of 9.64, shows the significant effect on preventing the ulceration.…”
Section: Peptic Activitymentioning
confidence: 99%
“…The fruits of the coconut palm are not nuts, but drupes 27 . it utilized as antiplasmodial 28 , menorrhagia 29 ,, antiulcerogenic ,wound healing (anti-inflammatory, anti-diabetic, antimicrobial, anti-neoplastic, antioxidant, anti-parasitic, insecticidal and cell proliferation of one or more parts for example coconut water, spadix, husk fiber, oil, flowers and mesocarp of coconut fruit are documented 30,31,32 .…”
Section: Datura Metelmentioning
confidence: 99%